Implementasi Kurikulum 2013 Melalui Model Problem Based Learning Pada Pembelajaran IPA untuk Meningkatkan Aktivitas dan Hasil Belajar Peserta Didik - Yulianingsih, Prita; Bhakti, Yoga Budi; Harjono, Harjono (Schrodinger Jurnal Ilmiah Mahasiswa Pendidikan Fisika, 2024)
This research aims to implement the 2013 curriculum through the problem-based learning (PBL) model in science education to improve the activity and learning outcomes of seventh-grade students at SMPIT Arrahmah, specifically on the classification of substances with concepts in Cycle I focusing on acids, bases, and salts, while Cycle II covers natural indicators. The study was conducted on a class of 20 students and one teacher. The research subjects were determined based on the consideration of the science teacher and the researcher. The learning model used was problem-based learning. Data were obtained through pre-tests before the lessons were conducted and post-tests after the lessons, along with student experiment activities and teacher activities during each cycle of the learning process. The pre-test and post-test were used to assess students' learning outcomes (gain index) in each cycle, as PBL was applied in the classroom. The evaluation tool for learning outcomes was multiple-choice tests to assess the improvement in students' understanding of mixtures, acids, bases, and salts. Based on the analysis of the learning process, improving students' activity and learning outcomes through the PBL model in science education resulted in an 82% improvement in activity (Cycle I) and 89% (Cycle II), teacher achievement in teaching increased from 79.31% (Cycle I) to 96% (Cycle II). Learning outcomes in the affective domain improved by 72% (Cycle I) and 96% (Cycle II), while the cognitive domain had a gain index of 0.44 (Cycle I, moderate category) and 0.64 (Cycle II, high category). The psychomotor domain increased from 75% (Cycle I) to 86% (Cycle II). The students' response to the PBL model in learning the human nervous system showed a positive response, with 92% liking science, 85% preparing for lessons, 85% understanding the material, 97% appreciating the presence of acids, bases, and salts in life, and 88% collaborating in groups.